A case study of core house design modification on simple housing : KPR Griya Mahoni Housing, West Aceh / Hissa Arfira, Bustari and Laina Hilma Sari - Arfira, Hissa; Bustari, Bustari; Sari, Laina Hilma (2018)
KPR Griya Mahoni Housing of West Aceh is a housing loan provided by banks to individual customers who will buy a house. Currently, the housing is in great demand, especially for those who have limited monthly incomes to build their own house as well as to buy it in cash. There are two types of houses offered by developers such as 36 type and 36 plus type which are designed with different space. Customers are able to choose the plan provided by the developer as desired. However, after the houses are occupied, many changes were done to fulfill residents’ individual needs. The condition leads to some problems such as the formation of space with poor openings, less air ventilation and windows, and unorganized building mass. Based on these problems the study was conducted to determine what factors influence the residents to change the house and to examine how the core housing changes in the KPR Griya Mahoni housing of West Aceh. This research used quantitative descriptive research method with data collection obtained through observation, interview, questionnaire, and documentation. Based on the results of the study 56.70% of the residents in KPR Griya Mahoni did expansion to the house. Some the factors that affect the changes in the KPR Griya Mahoni housing are increased income, land status, land area and completeness of facilities and basic infrastructure